Karakterisasi Unjuk Kerja Mesin 100 CC dengan Bahan Bakar Syngas - Rudy Sutanto; Pandri Pandiatmi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
Gasification is a process of converting carbon-containing compounds to convert both liquid and solid materials into fuel-capable gas (CO, H2, CO2, CH4, and H2O) through the combustion process with limited air supply. Gasification that we have known so far is gasification with coal feed and agricultural waste, but gasification with livestock waste feed has never been done. In this study the gasification feed material used horse dung biomass with a gas agent in the form of oxygen. The purpose of this study was to determine the effect of oxygen flow rate (4 variations namely 10, 15, 20 and 30 lt / min) in the process of gasification of horse dung (produced 4 fuels namely syngas A, syngas B, syngas C and syngas D) on the performance capabilities of a 100 cc engine. The stages of the research carried out were drying feed material, gasification process, syngas storage and testing on a 100 cc engine with various variations of rotation (4 variations namely 1500, 2500, 3500 and 4500 rpm). The results obtained from this study are the highest torque and effective power obtained in syngas A fuel for various engine speeds. At 4500 rpm, a torque of 6.7 Nm is obtained, while an effective power of 3156 Watts is used to test engine results using Syngas A fuel.